Distribution of Stepchildren's Rights in Inheriting According to Islam - Habib, Muhamad; Sari, Ruli Vita; Putra, Zakiyya Muflih Gusma; Sholeh, Mohamad; Fulianto, Eko; Gustini, Rahayu Pradita (Lembaga Penelitian dan Pendidikan (LPP) Mandala, 2024)
The distribution of stepchildren's rights in inheritance according to Islamic law is an important thing that we must know and need to understand. The technique for preparing this article uses research from previous research results after collecting several journals and information that has been searched through social media. Stepchildren in Islamic inheritance law are not directly classified as heirs because there is no hereditary cause (asbabul miirats). (deliberation). As a result, according to the general view, stepchildren do not automatically have the right to inherit their stepparent's inheritance. However, by using other alternatives (other methods) in Islamic inheritance law, stepchildren will not lose their right to receive protection from their parents, as the inherited children of their biological father and mother. And in Islamic inheritance law, stepchildren can inherit assets from the marriage of their biological father or new mother (their new family) by means of Qiyas and Wasiat Wajibah in the amount of 1/3. The aim is to find out the position and understanding of stepchildren's inheritance rights in Islamic inheritance law and how to obtain a share of stepchildren's inheritance rights in Islamic inheritance law.